Basement membrane and apocrine epithelial antigens in differential diagnosis between tubular carcinoma and sclerosing adenosis of the breast. - Ekblom, P (1984)
The distributions of defined basement membrane proteins in nine pure tubular carcinomas, 10 cases of sclerosing adenosis, and 15 ductal adenocarcinomas were compared. Sections of formalin fixed, paraffin embedded specimens were pretreated with pepsin and then immunostained for laminin, type IV collagen, and basement membrane proteoglycan, components specific for basement membranes. In sclerosing adenosis the tubules were surrounded by a continuous intact basement membrane composed of laminin, type IV collagen, and basement membrane proteoglycan, while the epithelium in the tubular carcinomas was negative for these proteins. The tumours were also analysed for the distribution of the apocrine epithelial antigen (AEA). In contrast to the benign lesions the tubular carcinomas expressed the AEA in a distinct non-polar fashion throughout the cell surface. In normal ducts and in adenosis the AEA was confined exclusively to the luminal surface. These studies suggest that there is a disturbance of cell polarity in tubular carcinomas. It is concluded that a combined analysis of basement membrane proteins and luminal surface antigens is a reliable and convenient way to differentiate between tubular carcinoma and sclerosing adenosis of the breast.